DETERMINATION OF FASCIOLA GIGANTICA E/S PROTEINS BY SDS-PAGE - Gödekmerdan, Ahmet; Kaplan, Mustafa (Fırat University, 2001)
Aim: The aim of this study was to examine excreatory-secretory (E/S) proteins obtained from mature F. gigantica by sodium dodecyl sulfide-polyacrylamide gel electrophores (SDS-PAGE) method. Materials and Methods: F. gigantica was obtained from bile ducts of infected sheep. In the SDS-PAGE, 10% separating gel was used and separation process was completed 150 V in 3.5 hours. Results: At the end of the SDS-PAGE examination, two extensively dense protein bands, approximately 65 and 70 kDa in size were visualised. Conclusion: We believe in that Fasciola gigantica cases can be diagnose in Turkey when the diagnostic methods are used routinely providing effective laboratory facilities to the clinicians.

Amaç: Bu çalışmada F. gigantica ekskretuvar-sekretuvar (E/S) proteinlerinin sodium dodecyl sulfide-polyacrylamide gel elektroforez (SDS-PAGE) yöntemi ile tanımlanması amaçlandı. Gereç ve Yöntem:Doğal olarak enfekte koyunların safra yollarından alınan erişkin F. gigantica'lar PBS'de 4 saat bekletilerek E/S proteinleri elde edildi. E/S proteinlerine SDS-PAGE'de %10'luk ayırıcı jelde 150 V sabit akımla 3.5 saat seperasyon işlemi yapıldı. Jel fikse edilerek %0.1 AgNO3 ile boyandı. Bulgular: Çalışmamızda F. gigantica E/S proteinlerinden 65 ve 70 kDa'luk oldukça yoğun iki protein bandı görüldü. Sonuç: Tanı yöntemlerinin rutin uygulamaya sokulması ile klinisyenlere etkin bir laboratuvar desteği sağlanması durumunda ülkemizde fasyoliyaz gigantica olgularının saptanabileceği düşüncesindeyiz.
FASCİOLA GİGANTİCA E/S PROTEİNLERİNİN SDS-PAGE İLE TANIMLANMASI